Comparative Effectiveness of Plain Balloon Angioplasty, Bare Metal Stents, Drug-Coated Balloons, and Drug-Eluting Stents for the Treatment of Infrapopliteal Artery Disease: Systematic Review and Bayesian Network Meta-analysis of Randomized Controlled Trials. (December 2016) - Katsanos, Konstantinos; Kitrou, Panagiotis; Spiliopoulos, Stavros; Diamantopoulos, Athanasios; Karnabatidis, Dimitris
Purpose: To report a Bayesian network meta-analysis of randomized controlled trials (RCTs) comparing bare metal stents (BMS), paclitaxel-coated balloons (PCBs), and drug-eluting stents (DES) with balloon angioplasty (BA) or with each other in the infrapopliteal arteries.Methods: Sixteen RCTs comprising 1805 patients with 1-year median follow-up were analyzed. Bayesian random effects binomial models were employed (WinBUGS). Relative treatment effects were expressed as odds ratios (ORs) with 95% credible intervals (CrI), and the cumulative rank probabilities were calculated to provide hierarchies of competing treatments. Quality of evidence (QoE) was assessed with the GRADE (grading of recommendations assessment, development, and evaluation) system. Sensitivity, heterogeneity, and consistency analyses were performed.Results: There was high QoE that infrapopliteal DES significantly reduced restenosis compared with BMS (OR 0.26, 95% CrI 0.12 to 0.51) and BA (OR 0.22, 95% CrI 0.11 to 0.45). Likewise, DES significantly reduced target lesion revascularization (TLR) compared with BA (OR 0.41, 95% CrI 0.22 to 0.75) and BMS (OR 0.26, 95% CrI 0.15 to 0.45). Paclitaxel-coated balloons also reduced TLR compared with BA (OR 0.55, 95% CrI 0.34 to 0.90) and BMS (OR 0.35, 95% CrI 0.18 to 0.67), but QoE was low to moderate. BA had lower TLR than BMS (OR 0.63, 95% CrI 0.40 to 0.99) with high QoE. DES was the only treatment that significantly reduced limb amputations compared with BA (OR 0.58, 95% CrI 0.35 to 0.96), PCB (OR 0.51, 95% CrI 0.26 to 0.98), or BMS (OR 0.38, 95% CrI 0.19 to 0.72) with moderate to high QoE. DES also significantly improved wound healing compared with BA (OR 2.02, 95% CrI 1.01 to 4.07) or BMS (OR 3.45, 95% CrI 1.41 to 8.73) with high QoE. Results were stable on sensitivity and meta-regression analyses without any significant publication bias or inconsistency.Conclusion: Infrapopliteal DES were associated with significantly lower rates of restenosis, TLR, and amputations and improved wound healing compared to BA and BMS. DES also significantly reduced amputations compared with PCB.